De novo characterization of the Goji berry (Lycium barbarium L.) fruit transcriptome and analysis of candidate genes involved in sugar metabolism under different CO2 concentrations. (16th March 2019) - Ma, Yaping; Reddy, Vangimalla R; Devi, Mura Jyostna; Song, Lihua; Cao, Bing
Abstract: Goji berry ( Lycium barbarum L.) is one of the important economic crops due to its exceptional nutritional value and medicinal benefits. Although reduced sugar levels in goji berry exposed to long-term elevated carbon dioxide (CO2 ) have been documented, the underlying molecular mechanisms remain unknown. The objective of this study was to explore the transcriptome of goji berry fruit under ambient and elevated CO2 concentrations and further to screen the differentially expressed genes (DEGs) for functions related to sugar metabolism. Fruit samples from goji berry exposed to ambient (400 μmol mol −1 ) and elevated (700 μmol mol −1 ) levels of CO2 for 120 days were analyzed for total sugar, carotenoid and flavone analysis. In this study, a reduction in total sugar and carotenoid levels in the fruits grown under elevated CO2 levels were observed. Fruit samples were also used to construct cDNA libraries using a HiSeqTM2500 platform. Consequently, 81, 100 unigenes were assembled, of which 35, 111 (43.3%) were annotated using various databases. Through DEGs analysis, it was found that 55 genes were upregulated and 18 were down-regulated in response to elevated CO2 treatment. Genes involved in the sugar metabolism and the related pathways were identified by Gene Ontology and Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis. Furthermore, three genes, LBGAE ( Lycium barbarum UDP-glucuronate 4-epimerase), LBGALA ( Lycium barbarum alpha-galactosidase) and LBMS ( Lycium barbarum malate synthase), associated with sugar metabolism were identified and discussed with respect to the reduction in the total sugar levels along with the enzymes acid invertase (AI), sucrose synthase (SS) and sucrose phosphate synthase (SPS) of the sucrose metabolism. This study can provide gene sources for elucidating the molecular mechanisms of sugar metabolism in the fruit of goji berry under elevated CO2 .